(untitled) (Research, Society and Development, 2021)
The development of new products is necessary to meet consumer demand, which increasingly presents specific needs and desires. In this sense, the market for zero lactose products is constantly growing, in order to meet this demand. It is estimated that for every 10 Brazilians, 7 are intolerant, and for some, intolerance has been present since the first moments of life. In view of this and seeking to assess the current market scenario in the context of lactose-free products, an online questionnaire was applied and a dessert of the frozen pudding type without lactose was carried out, which underwent sensory evaluation and purchase intention as a method. study to investigate the market potential of this product. The online questionnaire resulted in 521 responses and pointed out that 22.8% were lactose intolerant, while 71.2% had no intolerance. The sensory analysis of iced pudding without lactose showed an acceptance above 70% in all attributes on the hedonic scale and 92% of the volunteers answered that they would certainly or probably buy the product. It is concluded, therefore, that the developed zero lactose pudding pleased both intolerant and non-intolerant evaluators, presenting a promising alternative in the scenario of lactose-free products because, in addition, it has a similar cost to a traditional pudding.